World Bank Research Digest, Vol. 11(1) - World Bank (World Bank, Washington, DC, 2017)
This issue includes the following headings: Insights from World Bank Research on Trade and Globalization; What Drives Differences in Exporter Behavior across Countries? The Rising Domestic Content of Chinese Exports; The Quality Effects of Exporting to High-Income Countries; Labor Market Frictions and Trade Adjustment Costs in Developing Countries; How Product Standards AffectFirms' Export Decisions; How Services Reform Helped Revive Indian Manufacturing; Are the Benefits of Export Support Durable? Resource Rents and Local Development in Post-Apartheid South Africa; Are Politically Connected Firms More Likely to Evade Import Tariffs and Other Taxes? Trade Agreements under Threat; and Recent World Bank Research Publications and Papers on Trade and Globalization